Sobre a existência de folheações por soluções do problema exterior de Dirichlet para a equação das hipersuperfícies mínimas - Pedra, Filipe Almeida (2024)
Given an exterior C 2,α-domain Ω ⊂ R n , with n ≥ 3, in this work we study the existence of a foliation of an open subset U ⊂ Ω × R, with ∂Ω ⊂ ∂U, by solutions to the exterior Dirichlet problem for the minimal hypersurfaces equation in Ω with zero boundary data. Additionally, we analyze the behavior at ∂Ω and at infinity of the leaves of this foliation and the role played by the geometry of the domain in this context.